2016
DOI: 10.1093/sf/sow064
|View full text |Cite|
|
Sign up to set email alerts
|

From Heterogeneity to Concentration: Latino Immigrant Neighborhoods and Collective Efficacy Perceptions in Los Angeles and Chicago

Abstract: Latino immigrant presence in urban neighborhoods has been linked with reduced neighborhood cohesion in social disorganization-based ethnic heterogeneity hypotheses and enhanced cohesion in immigration revitalization approaches. Using the 2000-2002 Los Angeles Family and Neighborhood Survey and the 1994-1995 Project on Human Development in Chicago Neighborhoods Community Survey, we explore the association between Latino immigrant concentration and both levels of, and agreement about, neighborhood collective eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
48
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 55 publications
6
48
1
Order By: Relevance
“…In contrast, when immigrants reach a large proportion of the neighborhood population, a variety of community‐wide externalities may be more likely to emerge. Browning, Dirlam, and Boettner () documented such a nonlinear effect of community immigrant concentration on levels of collective efficacy, and we suggest that a similar pattern may exist for legal cynicism. Thus, as shown in the summary of hypotheses in table , on the basis of the legal cynicism framework, we anticipate a negative association between the percentage of neighborhood residents who are foreign born and the likelihood of crime reporting by victims of crime that strengthens, and perhaps only emerges, at high levels of percent foreign born (H1).…”
Section: Research Backgroundsupporting
confidence: 67%
See 2 more Smart Citations
“…In contrast, when immigrants reach a large proportion of the neighborhood population, a variety of community‐wide externalities may be more likely to emerge. Browning, Dirlam, and Boettner () documented such a nonlinear effect of community immigrant concentration on levels of collective efficacy, and we suggest that a similar pattern may exist for legal cynicism. Thus, as shown in the summary of hypotheses in table , on the basis of the legal cynicism framework, we anticipate a negative association between the percentage of neighborhood residents who are foreign born and the likelihood of crime reporting by victims of crime that strengthens, and perhaps only emerges, at high levels of percent foreign born (H1).…”
Section: Research Backgroundsupporting
confidence: 67%
“…Browning et al. () found support for this idea in Los Angeles and Chicago, where growth in the percent foreign born beyond approximately 40–50 percent yielded significant increases in the levels of collective efficacy. This pattern represents another reason that percent foreign born may exhibit an accelerating positive association with victim crime reporting rates.…”
Section: Research Backgroundmentioning
confidence: 98%
See 1 more Smart Citation
“…Whereas psychologists have considered this possibility in the context of small groups, prior neighborhood research rarely empirically examines this possibility. One recent exception considers how Latino immigrant concentration shapes variability in collective efficacy assessments at the tract level, in an effort to address the tension between ethnic heterogeneity and immigrant revitalization hypotheses (Browning et al 2016). The authors found a nonlinear effect such that at low levels of concentration, increasing Latino immigrant presence has a positive association with variability (e.g., greater disagreement), while at high levels of concentration, the effect becomes negative.…”
Section: Variability Within the Neighborhoodmentioning
confidence: 99%
“…The prior focus of Browning et al (2016) on Latino immigrant concentration provides just one example of the types of contexts in which social distance is salient. For example, prior research found that gentrification processes often lead to stable or increased diversity (Freeman 2009).…”
Section: Variability Within the Neighborhoodmentioning
confidence: 99%